Clinical, imaging, and follow-up observations of patients with anti-GABAB receptor encephalitis. (4th May 2017) - Qiao, Song; Zhang, Yin-Xi; Zhang, Bi-Jun; Lu, Ru-Yi; Lai, Qi-Lun; Chen, Lin-Hui; Wu, Jiong
Abstract : Purpose : Anti-gamma-aminobutyric acid B (anti-GABAB ) receptor encephalitis is a newly described type of autoimmune encephalitis. We report a case series of patients diagnosed with anti-GABAB receptor encephalitis in China, focusing on their presentations, laboratory and imaging results, and outcomes, as well as the treatment strategies which were employed. Methods : Data from patients diagnosed with anti-GABAB receptor encephalitis in the Second Affiliated Hospital, School of Medicine, Zhejiang University, from January 2014 to June 2015 were retrospectively collected and analyzed. Based on specific diagnostic criteria, seven cases were included. Results : Six of the seven patients were males, and a median age at presentation of 56 years (range: 4–71 years). Seizures were the most common initial symptom, and all patients developed symptoms of typical limbic encephalitis during their disease course. Additional types of autoantibodies were identified in four patients. After presentation, three patients were found to have small cell lung cancer and one patient was eventually diagnosed with thymoma. All patients accepted first-line immune therapy, but only one chose tumor treatment. The three tumor-free patients had a good outcome, whereas those with tumors had a poor one. Finally, there were no relapses during follow-up. Conclusion : Anti-GABAB receptor encephalitis is a rare, unique autoimmune disease, and is often associated with tumors. It should be considered in the differential diagnosis for middle and senior-aged patients who present with predominantly limbic encephalitis symptoms. Importantly, earlier recognition of this potentially treatable condition could improve its overall prognosis.